Mimiviruses Interfere With IκBα Degradation - dos Santos Oliveira, Juliana; Oliveira, Dahienne Ferreira; Essus, Victor Alejandro; Nunes, Gabriel Henrique Pereira; Honorato, Leandro; Peralta, José Mauro; Nimrichter, Leonardo; Guimarães, Allan Jefferson; Foguel, Debora; Filardy, Alessandra Almeida; Cortines, Juliana R. (Frontiers in Virology, 2022)
Many aspects of giant viruses biology still eludes scientists, with viruses such as Acanthamoeba polyphaga mimivirus (APMV) and Tupanvirus (TPV) possessing large virions covered by fibrils and are cultivated in laboratories using Acanthamoeba cells as hosts. However, little is known about the infectivity of these giant viruses in vertebrate cells. In the present study, we investigated the consequences of the incubation of APMV and Tupanvirus with mammalian cells. These cells express Toll-like receptors (TLR) that are capable of recognizing lipopolysaccharides, favoring the internalization of the antigen and activation of the inflammatory system. By using a lineage of human lung adenocarcinoma cells (A549), we found that APMV and TPV virus particles interact and are internalized by these cells. Furthermore, when treating cells with a fibriless variant of APMV, the M4 strain, there was no significant loss of viability, reinforcing the roles of fibrils in cell activation. In addition, we found an upregulation of TLR4 expression and an expected down regulation of IκBα in A549 APMV or TPV-infected cells compared to non-infected cells. Our results suggest that mimiviruses are able to interact with innate immune components such as TLR4, inducing their downstream signaling pathway, which ultimately active proinflammatory responses in lung cells.